2008
DOI: 10.2172/1022437
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Acoustic-tagged and PIT-tagged Juvenile Salmonids

Abstract: PREFACENumerous research tools and technologies are currently being used to evaluate fish passage and survival to determine the impacts of the Federal Columbia River Power System (FCRPS) on endangered and threatened juvenile salmonids. Among these are the PIT tag, balloon tag, hydroacoustic evaluation, radio telemetry, and acoustic telemetry. Each has advantages and disadvantages, but options are restricted in some situations because of limited capabilities of a specific technology, lack of detection capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Fish were maintained in the artificial seawater system through the remainder of the holding period. Timing of transfer to seawater was based primarily on yearling travel time to ocean entry [41]. For subyearlings, travel time during the summer migration varies considerably [42]; nevertheless, we transferred these groups to seawater at holding day 15 for comparison purposes.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…Fish were maintained in the artificial seawater system through the remainder of the holding period. Timing of transfer to seawater was based primarily on yearling travel time to ocean entry [41]. For subyearlings, travel time during the summer migration varies considerably [42]; nevertheless, we transferred these groups to seawater at holding day 15 for comparison purposes.…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…We do not know how the implanted tag may have affected its behavior. Hockersmith et al (2008), researching tag effects studies for the same types of transmitters and species of fish we studied, reported that travel times in most reaches were not significantly different between fish tagged with JSATS transmitters and fish tagged with PIT tags. Furthermore, laboratory experiments by Hockersmith et al (2008) showed low mortalities (<4.5%) of yearling Chinook salmon for both tag types.…”
Section: Discussionmentioning
confidence: 97%
“…Hockersmith et al (2008), researching tag effects studies for the same types of transmitters and species of fish we studied, reported that travel times in most reaches were not significantly different between fish tagged with JSATS transmitters and fish tagged with PIT tags. Furthermore, laboratory experiments by Hockersmith et al (2008) showed low mortalities (<4.5%) of yearling Chinook salmon for both tag types. For subyearling Chinook salmon, mortality among control and PIT-tag treatments ranged up to 7.7%, while integrated and nonintegrated treatments had slightly higher rates (up to 8.3% and 7.9%, respectively).…”
Section: Discussionmentioning
confidence: 97%
“…PLOS ONE Marking recovery tank additive Subyearling Chinook salmon [63] Surgical work surface coating Juvenile pacific lamprey [64], juvenile salmonids [65] https://doi.org/10.1371/journal.pone.0288056.t002…”
Section: Synthetic Polymermentioning
confidence: 99%